This preview shows page 1. Sign up to view the full content.
Unformatted text preview: y p ( t ) to the expression for y h ( t ). Thus, we obtain y ( t ) = c 1 e t + c 2 te t te t + te t ln  t  = c 1 e t + ( c 2 1) te t + te t ln  t  . If we let C 1 = c 1 and C 2 = c 2 1, we can express this general solution in the form y ( t ) = C 1 e t + C 2 te t + te t ln  t  . 215...
View
Full
Document
 Spring '10
 Hald,OH
 Math, Differential Equations, Linear Algebra, Algebra, Equations

Click to edit the document details